APPLICATION OF PLASTER CAST AND WIRING FOR UNILATERAL HORN FRACTURE REPAIR IN A KANKREJ BULLOCK: A CASE REPORT - Sama, AI; Vala, AK; Gohil, KM; Mer, DR; Kalasariya, RM; Parikh, PV (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
In cattle, horn fracture occurs as a result of trauma due to fighting or an accident. Incomplete fracture, if not treated early, may be associated with complications like complete fracture following repeated injury and frontal sinusitis and then dehorning is the solution to the problem (Tyagi and Singh, 1983). Incomplete fracture of horn involving its distal portion may heal if properly immobilized, but immobilization itself is difficult (Venugopalan, 1994). Therefore, an effort has been made to document a case report on immobilization of simple incomplete horn fracture with plaster cast and wiring in a bullock.